Analysis of the ZVS operating range of input-series output-series DC–DC DAB converters for MV DC microgrids using different modulators to control the power flow - Garrido, Daniel Oscar (2025)
This paper analyzes the input-series-output-series (ISOS) connection of dual active bridge (DAB) modules for medium voltage DC microgrids using different modulators: first using a unique modulator that allows controlling of the power flow of all modules, which is a more straightforward solution, and then using independent modulators to facilitate the voltage balance and the power transference of each one. In this analysis, parametric differences between the modules are considered, and the voltage distribution between the modules, the ZVS conditions, and the transferred power as a function of the main converter parameters design are obtained. Finally, experimental results of a scaled-down 500~W prototype demonstrate the proposal´s feasibility.